IS ENTRY TEST NEEDED FOR MEDICAL COLLEGE ADMISSIONS? - Abdul Haque (Journal of University Medical & Dental College, 2020)
Entry test for medical students is a good idea because of two reasons: firstly to align our educational system with modern requirements keeping pace with international standards; and secondly to nullify the bias caused by different levels of scrutiny employed by various educational boards. However, it required that the Government started to develop a uniform, modernized education system which would eventually make entry tests unnecessary. But unfortunately, this has not happened. We still have different education systems (F.Sc., A level etc.) and still the students are judged by different yardsticks by educational boards.